2012
DOI: 10.1186/1742-4755-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of legal abortion in Nepal: a model for rapid scale-up of high-quality care

Abstract: Unsafe abortion's significant contribution to maternal mortality and morbidity was a critical factor leading to liberalization of Nepal's restrictive abortion law in 2002. Careful, comprehensive planning among a range of multisectoral stakeholders, led by Nepal's Ministry of Health and Population, enabled the country subsequently to introduce and scale up safe abortion services in a remarkably short timeframe. This paper examines factors that contributed to rapid, successful implementation of legal abortion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
116
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 11 publications
1
116
0
2
Order By: Relevance
“…The cost of a legal abortion ranges from 800 Rs to 2,000 Rs ($11.33 USD to $28.33 USD) (MOHP and CREHPA 2007) relative to mean annual income 1,978 Rs in 2004 (Central Bureau of Statistics 2004:37). Government policy stipulates that poor women are entitled to abortion services free of charge, but eligibility criteria have not been clearly defined, and in practice, they tend not to receive any preferential treatment (MOHP and CREHPA 2007;Samandari et al 2012). Comparisons with the cost of illegal abortions are difficult; five case studies in MOHP et al (2006) reported considerable variation (200,500,700,3,000,and 8,000 Rs).…”
Section: The Nepalese Natural Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of a legal abortion ranges from 800 Rs to 2,000 Rs ($11.33 USD to $28.33 USD) (MOHP and CREHPA 2007) relative to mean annual income 1,978 Rs in 2004 (Central Bureau of Statistics 2004:37). Government policy stipulates that poor women are entitled to abortion services free of charge, but eligibility criteria have not been clearly defined, and in practice, they tend not to receive any preferential treatment (MOHP and CREHPA 2007;Samandari et al 2012). Comparisons with the cost of illegal abortions are difficult; five case studies in MOHP et al (2006) reported considerable variation (200,500,700,3,000,and 8,000 Rs).…”
Section: The Nepalese Natural Experimentsmentioning
confidence: 99%
“…Under the policy, senior gynecologists from central and regional hospitals as well as from some non-governmental organizations (NGOs) and private clinics were trained to become both the first legal abortion providers as well as safe abortion trainers themselves. With the aim of rapid national scale-up, training then cascaded from regional and zonal hospitals to public district hospitals (Samandari et al 2012). The private sector (primarily Marie Stopes International and the Family Planning Association of Nepal) also "fill[s] an important niche in urban areas" (Samandari et al 2012:4) and is less prevalent in rural areas, which were home to 83 % of the Nepalese population according to the 2011 population census.…”
Section: The Nepalese Natural Experimentsmentioning
confidence: 99%
“…1 Previous laws did not allow abortion under any circumstances and many women who had had an abortion were imprisoned. 2 The introduction of legal abortion has been characterized by a committed effort by the Ministry of Health and Population and nongovernmental organizations to rapidly scale up access to safe abortion. Manual vacuum aspiration services became available in 2004; second-trimester procedures were introduced in 2007; and senior nurses who had prior training in post-abortion care began providing services in 2008.…”
mentioning
confidence: 99%
“…Manual vacuum aspiration services became available in 2004; second-trimester procedures were introduced in 2007; and senior nurses who had prior training in post-abortion care began providing services in 2008. 2 Manual vacuum aspiration was the only safe abortion method used until 2009 in Nepal. In line with the Safe Abortion Service Directives 2065 B.S.…”
mentioning
confidence: 99%
“…It is illegal if it is done for fetal sex selection and when abortion is performed under coercion and without the consent of the woman. In the case of minors (< 16 yrs of age) or mental incompetence, a legal guardian must give the consent 3,12 .…”
mentioning
confidence: 99%